Zabójstwa „honorowe” w Pakistanie – analiza The Qisas and Diyat Act 2004 - Sadowa, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The main aim of the article is to analyze the Pakistani legal regulations regarding honour killings. In the introduction, the author points out the great scale of honour killings in Pakistan and the main contributing factors. Further along, the article presents the main features of classic Islamic criminal law and a brief analysis of the Qisas and Diyat Act. Finally, the author offers an in-depth analysis of the two amendments to the Pakistan Criminal Code that directly concern honour killings
Keywords: Pakistan; zabójstwa honorowe; muzułmańskie prawo karne; przemoc honorowa; islam; kobiety; przemoc